CATIONIC ENVIRONMENT IN SILICATE GLASSES STUDIED BY NEUTRON DIFFRACTION WITH ISOTOPIC SUBSTITUTION - Cormier L.; Calas G.; Gaskell P.H. (My University, 2001)
The method of neutron diffraction coupled with isotopic substitution is presented and recent investigations on the environment around cations in silicate (Ti in K2O.TiO2.2SiO2, Ca and Ni in 2CaO.NiO.3SiO2) and aluminosilicate (Li in Li2O.Al2O3.2SiO2) glasses are reviewed. The examination of the cation-centered pairs obtained from the first difference function presents striking similarities for all investigated cations. These functions indicate a well-defined short- and medium-range environment around cations. The local site generally presents a lower coordination number than that found in the crystals of similar composition. The environment around Ti in vitreous K2O.TiO2.2SiO2 corresponds to a square-based pyramid and direct TiO5-TiO5 linkages were observed experimentally in the second difference function, contrary to crystals. A detailed description of the cation site distortion for Li and Ca may be given by this method. The distribution of cations at medium range, which can be extracted by the double difference method, reveals the presence of cation-rich regions in silicate glasses. The cation-cation distances often indicate a two-dimensional character in the cationic organization. On the contrary, Li-aluminosilicate glass shows a more homogeneous cation distribution, in relation with the charge-compensating role of Li in this glass. This non-homogeneous distribution of cations may be related to the nano-inhomogeneities proposed in the models of supercooled liquids.
Keywords: GLASSES; STRUCTURE; MEDIUM-RANGE ORDER; NEUTRON DIFFRACTION; ISOTOPIC SUBSTITUTION